294 Stem Cell Enriched Fat Grafts Versus Autologous Fat Grafts for Facial Reconstruction: A Systematic Review and Meta-Analysis. (19th August 2022) - Karam, M; Abul, A; Kahlar, N; Naik, A; Tay, J; Rahman, S; Matteucci, P
Abstract: Aim: To compare the results of stem cell-enhanced fat grafting to autologous fat grafting for face reconstruction. Method: A systematic review and meta-analysis were carried out in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) Guidelines, and an electronic search was carried out to identify all Randomised Controlled Trials (RCTs), case control studies, and cohort studies comparing the outcomes of stem cell-enrichment fat grafting versus routine fat grafting for facial reconstruction. The primary outcome measures were volume retention and infection rate. Secondary outcome measures included post-surgery patient satisfaction, redness and swelling, fat necrosis, cysts, and operation time. For the analysis, fixed and random effects modelling were utilised. Results: Eight studies with a total of 275 participants were assessed. In terms of mean volume retention, there was a significant difference between the stem cell-enrichment fat grafting and routine grafting groups (standardised Mean Difference [MD] = 2.49, P 0.00001). However, there was no significant difference in infection rates between the two groups (OR = 0.36, P = 0.30). Except for the operation duration, which was shorter in the latter, the intervention group had similar results to the control group for all secondary outcomes. Conclusions: When compared to conventional fat grafting, stem cell-enriched fat grafting is a better alternative for facial reconstruction surgery since it enhances mean volume retention and does not worsen patient satisfaction or surgical complications.